If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 8 = 6x + -3 Reorder the terms: 8 + 4x = 6x + -3 Reorder the terms: 8 + 4x = -3 + 6x Solving 8 + 4x = -3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 8 + 4x + -6x = -3 + 6x + -6x Combine like terms: 4x + -6x = -2x 8 + -2x = -3 + 6x + -6x Combine like terms: 6x + -6x = 0 8 + -2x = -3 + 0 8 + -2x = -3 Add '-8' to each side of the equation. 8 + -8 + -2x = -3 + -8 Combine like terms: 8 + -8 = 0 0 + -2x = -3 + -8 -2x = -3 + -8 Combine like terms: -3 + -8 = -11 -2x = -11 Divide each side by '-2'. x = 5.5 Simplifying x = 5.5
| y-5=10(x-1) | | 4n=5 | | P-8+4p= | | 9+12=711 | | 25=q+14 | | 5(4a+7)=3(8a+a) | | 7+6n+4-3n= | | 5(x+2)-3(x-4)=7-x | | 8-7p=12-5p | | Y=sec(x^3) | | 8y+43-7y=75 | | 4c-5(x+1)+11=0 | | Y=3tan*4x | | x+(x*.0875)=20.12 | | 5(2x-7)=0 | | 2y+x=8.5 | | 2x^3+10x^2-2x-10=0 | | 6x+29=65 | | 4x=-2x-42 | | 3x+2.5=4x-35 | | 4(2-2y)+6=2(7+4y) | | 18x-3y=6 | | 2+2m=4m+5 | | -3x+3/5+1/5=2(4-x)/5 | | -13-(3m+4)= | | (1-u)(2u-7)=0 | | x-7=(2x-4) | | -9x+6y=72 | | 1-4j=2j | | Y=cos(3x) | | 8+2(3a-5)-(6a-8b*b)-4b*b= | | 8x+4y=-56 |